(untitled) (Journal of Health Sciences, 2020)
Introduction: Alocasia denudata is a herbal plant used by traditional healers as a wound healing agent and its potential as a healer has been proven scientifically. Normally, wounded tissue offers the opportunity for microflora to adhere, colonize, invade, and infect the surrounding healthy tissue. Therefore, the aim of this study is to assess the antimicrobial effect of A. denudata on selective oral pathogen as well as to analyze its phytochemical compound. Methods: The stem of A. denudata was extracted with 80% ethanol solution, freeze-dried, and sent to poison center to analyze its phytochemical constituents. The bioassay applied for determining the antimicrobial effect employs the well agar diffusion method to the selected Gram-positive oral bacteria; Streptococcus mutans, Staphylococcus aureus, Enterococcus faecalis, and non-oral pathogen Streptococcus pyogenes. These bacteria were incubated and the inhibition zone was recorded. Results: Our results showed that the mean yield of extraction was 12.8% and that the different concentrations of A. denudata show no antimicrobial effects toward the selected Gram-positive oral pathogen including non-oral pathogen bacteria. However, the gas chromatography–mass spectrometry result showed that antimicrobial compound is present along with anti-inflammatory and antioxidant compounds but showed no effect on the oral pathogen. Conclusion: A. denudata extract has antimicrobial compound but did not show antimicrobial activity toward the selected Gram-positive oral pathogen.